Buddhist Ecology and Environmental Ethics: A Multiple-Case Study in Indonesia - Acep, Lauw (STAB Kertarajasa, 2025)
This study aims to understand how Buddhist ecological ethics contribute to sustainable living in four Indonesian communities. Employing a multi-case qualitative study approach, the research collected data through 28 semi-structured interviews, 40 hours of participant observation, and document analysis between 2022 and 2024. Thematic analysis revealed three key themes: (1) Ritualized reforestation as spiritual practice, where forest greening activities are not only ecological initiatives but also integrated into spiritual practices in line with Buddhist principles of interdependence and non-harming; (2) Integration of agroforestry and livelihood security, which shows that agroforestry practices are an integral part of the community's livelihood, enhancing food security and promoting biodiversity and soil health; and (3) Mindfulness-based environmental education, which explores how Buddhist principles are integrated into environmental education programs to strengthen a deeper connection with nature and encourage sustainable behavior. The findings of this study highlight the role of Buddhist ethics in shaping local environmental stewardship and offer important implications for community-based sustainability policies.